A qualitative study of antiretroviral therapy adherence interruptions among young Latino men who have sex with men with HIV: Project D.A.I.L.Y. Issue 7 (3rd July 2021) - Sheehan, Diana M.; De La Cruz, Yazmine; Ramírez-Ortiz, Daisy; Swendeman, Dallas; Muñoz-Laboy, Miguel; Duncan, Dustin T.; Cano, Miguel Ángel; Devieux, Jessy G.; Trepka, Mary Jo
ABSTRACT: Consistent antiretroviral therapy (ART) adherence is necessary for HIV viral suppression. However, adherence may fluctuate around daily routines and life events, warranting intervention support. We examined reasons for ART adherence interruptions, using in-depth, semi-structured qualitative interviews, among young (18–34-year-old) Latino men who have sex with men (YLMSM) with HIV. Interviews ( n = 24) were guided by the Theory of Planned Behavior, the Information-Motivation-Behavioral Skills Theory, and the Socio-Ecological Model. Two coders independently coded transcripts using NVivo 12 software and synthesized codes into themes using Thematic Content Analysis. Results suggested 4 primary influences on ART adherence interruptions: (1) HIV diagnosis denial, (2) breaks in daily routine, (3) substance use, and (4) HIV status disclosure. Participant quotes highlighted routinization of pill-taking and planning ahead for breaks in routine as critically important. The narrative suggested modification of pill-taking routines during alcohol use, and that periods most vulnerable for long-term interruptions in ART adherence were following an HIV diagnosis and during periods of drug use. Support at the time of HIV diagnosis, including a plan for routinization of pill taking, and adaptive interventions incorporating real-time support during breaks in routines and substance use episodes may be one way to help YLMSM adhere to ARTs.